CONSERVATIVE APPROACH TO THE MANAGEMENT OF EXTENSIVE ODONTOGENIC KERATOCYST IN THE MANDIBLE WITH RISK OF PATHOLOGICAL FRACTURE (REMUNOM, 2026)
The present clinical case report aims to describe the conservative surgical management of an extensive odontogenic keratocyst (OK) in the posterior mandibular region, associated with an impacted tooth and near the mandibular canal. A 21-year-old female patient presented with pain and paresthesia in the left mandibular area. Panoramic radiography and cone-beam computed tomography (CBCT) revealed a well-defined, multilocular radiolucent lesion involving the impacted tooth 38 and overlapping the mandibular canal. Initial treatment consisted of an incisional biopsy and cyst decompression, aiming to reduce lesion volume and minimize neurosensory risk. Clinical and radiographic follow-up demonstrated progressive reduction of the cystic cavity and thickening of the cortical bone, while histopathological examination confirmed the diagnosis of odontogenic keratocyst. The patient progressed without pain and with stable paresthesia, maintaining adequate hygiene and good adaptation to the decompression device. The two-stage approach proved effective for initial lesion control and for safely planning definitive treatment, reinforcing that in large lesions located near the inferior alveolar nerve, decompression followed by definitive therapy represents a conservative, predictable, and safe strategy.